Geometrical Patterning and Constituent Cell Heterogeneity Facilitate Electrical Conduction Disturbances in a Human Induced Pluripotent Stem Cell-Based Platform: An In vitro Disease Model of Atrial Arrhythmias - Nakanishi, Hiroyuki; Lee, Jong-Kook; Miwa, Keiko; Masuyama, Kiyoshi; Yasutake, Hideki; Li, Jun; Tomoyama, Satoki; Honda, Yayoi; Deguchi, Jiro; Tsujimoto, Shinji; Hidaka, Kyoko; Miyagawa, Shigeru; et al. (Frontiers in Physiology, 2019)
Ectopic foci from pulmonary veins (PVs) comprise the main trigger associated with the initiation of atrial fibrillation (AF). An abrupt anatomical narrow-to-wide transition, modeled as in vitro geometrical patterning with similar configuration in the present study, is located at the junction of PVs and the left atrium (LA). Complex cellular composition, i.e., constituent cell heterogeneity, is also observed in PVs and the PV-LA junction. High frequency triggers accompanied with anatomical irregularity and constituent cell heterogeneity provoke impaired conduction, a prerequisite for AF genesis. However, few experiments investigating the effects of these factors on electrophysiological properties using human-based cardiomyocytes (CMs) with atrial properties have been reported. The aim of the current study was to estimate whether geometrical patterning and constituent cell heterogeneity under high frequency stimuli undergo conduction disturbance utilizing an in vitro two-dimensional (2D) monolayer preparation consisting of atrial-like CMs derived from human induced pluripotent stem cells (hiPSCs) and atrial fibroblasts (Fbs). We induced hiPSCs into atrial-like CMs using a directed cardiac differentiation protocol with the addition of all-trans retinoic acid (ATRA). The atrial-like hiPSC-derived CMs (hiPSC-CMs) and atrial Fbs were transferred in defined ratios (CMs/Fbs: 100%/0% or 70%/30%) on manually fabricated plates with or without geometrical patterning imitating the PV-LA junction. High frequency field stimulation emulating repetitive ectopic foci originated in PVs were delivered, and the electrical propagation was assessed by optical mapping. We generated high purity CMs with or without the ATRA application. ATRA-treated hiPSC-CMs exhibited significantly higher atrial-specific properties by immunofluorescence staining, gene expression patterns, and optical action potential parameters than those of ATRA-untreated hiPSC-CMs. Electrical stimuli at a higher frequency preferentially induced impaired electrical conduction on atrial-like hiPSC-CMs monolayer preparations with an abrupt geometrical transition than on those with uniform geometry. Additionally, the application of human atrial Fbs to the geometrically patterned atrial-like hiPSC-CMs tended to further deteriorate the integrity of electrical conduction compared with those using the atrial-like hiPSC-CM alone preparations. Thus, geometrical narrow-to-wide patterning under high frequency stimuli preferentially jeopardized electrical conduction within in vitro atrial-like hiPSC-CM monolayers. Constituent cell heterogeneity represented by atrial Fbs also contributed to the further deterioration of conduction stability.